Alternate wet/dry irrigation in rice cultivation: a practical way to save water and control malaria and Japanese encephalitis? - Hoek, Wim van der; Sakthivadivel, Ramaswamy; Renshaw, M.; Silver, J.B.; Birley, M.H.; Konradsen, Flemming (International Water Management Institute, 2001)
More irrigated land is devoted to rice than to any other crop. A method to save water in irrigated rice cultivation is the intermittent drying of the rice fields, known as alternate wet/dry irrigation (AWDI). This report reviews previous studies in AWDI, with a focus on mosquito vector control, water saving, and rice yields. Examples are provided from a number of countries.